Rent Creation and Rent Containment : The Political Economy of Telecommunications in Mexico, South Africa, and Turkey - Atiyas, Izak; Levy, Brian; Walton, Michael (World Bank, Washington, DC, 2017)
The evolution of the telecommunications sector is of keen interest from both a development and a political economy perspective. Telecommunications is critical to economic dynamics, to the quality of life, to social service provision, and to citizen engagement. This paper explores the political economy of telecommunications in three middle income countries - Mexico, South Africa, and Turkey. It undertakes an interpretation of the processes at work through the lens of these comparative cases. It is also intended as a case study of a set of broader questions over the development process, as this is shaped by the central nexus of relations between business and state actors. The paper is specifically concerned with the following questions: how does policy change in real polities, in terms of both policy design and implementation?; how is this shaped by the underlying nature of business-state relations, and to the overall political settlement in a country?; is there a tendency for economic entrenchment in typical middle income countries?; by this the authors mean consolidation of economic activities in ways that support sustained economic rents, underpinned by various mixes of regulatory capture and market power. And what countervailing forces are there to support a more dynamic and competitive equilibrium?; how is the state understood in the context of these business-state relations?; how is it useful to deconstruct the state, and in particular, do checks and balances institutions have the autonomy to provide a check on entrenchment?; and how do these processes interact with technological change? These questions relate to the broader issue of whether governance arrangements can countervail unequal political and economic power in ways that foster inclusive development.